A Case Study Based on a Spontaneous Discourse of Greek–Hungarian Bilinguals in Respect of Interjections, Swear Words and Syntactical Mistakes, as Regards Gender - Ürmösné Simon, Gabriella (Magyar Rendészet, 2017)
This case study reflects how gender linguistic discrepancies emerge from monolingual and bilingual spontaneous speed sequences. It touches upon phonetic, phonological, morphological, syntactical and communicative strategic levels, but highlights data deriving from the frequency of interjections, swear words and syntactical mistakes. The prior objective of the two corpora based study is to prove that bilinguals are more flexible individuals, and therefore less clear cut discrepancies are revealed in the discourse of the two genders.